Biosafety and Biosecurity: A Relative Risk-Based Framework for Safer, More Secure, and Sustainable Laboratory Capacity Building - Dickmann, Petra; Sheeley, Heather; Lightfoot, Nigel (Frontiers in Public Health, 2015)
Background: Laboratory capacity building is characterized by a paradox between endemicity and resources: Countries with high endemicity of pathogenic agents often have low and intermittent resources (water, electricity) and capacities (laboratories, trained staff, adequate regulations). Meanwhile, countries with low endemicity of pathogenic agents often have high containment facilities with costly infrastructure and maintenance governed by regulations. The common practice of exporting high biocontainment facilities and standards is not sustainable and concerns about biosafety and biosecurity require careful consideration. Methods: A group at Chatham House developed a draft conceptual framework for safer, more secure and sustainable laboratory capacity building. Results: The draft generic framework is guided by the phrase ‘LOCAL – PEOPLE – MAKE SENSE’ that represents three major principles: capacity building according to local needs (local) with an emphasis on relationship and trust-building (people) and continuous outcome and impact measurement (make sense). Conclusions: This draft generic framework can serve as a blueprint for international policy decision-making on improving biosafety and biosecurity in laboratory capacity building, but requires more testing and detailing development.